Bach the borrower - Carrell, Norman (London George Allen & Unwin LTD, 1967)
The author's purpose is to explore and document Bach's borrowings and adaptations within his own oeuvre. Bach reworked and adapted his own compositions and his seeming indifference to the medium employed can be reviewed with the aid of this voluminous record, with commentary, of his adaptations, recompositions or transcriptions.